Understanding the development of depression through emotion beliefs, emotion regulation, and parental socialisation - Susanne Peter; Olivia S. Riddle; Bonamy R. Oliver; Matthew P. Somerville (Scientific Reports)
Abstract The capacity to understand and regulate emotions flexibly and productively is a key driver of mental health and well-being. Parents’/carers’ role in emotion socialisation—specifically, their response to children’s expressions of emotion—has significant influence on the development of these processes. We examined emotion controllability beliefs (ECBs) and cognitive reappraisal as underlying mechanisms of the relationship between recalled parental emotion responses and depression across two studies. In Study 1 (N = 215, 65.6% female, M age = 29.10), we found that supportive parental responses were associated with lower levels of depression via increased use of cognitive reappraisal. Study 2 (N = 410, 51.7% female, M age = 46.24) replicated the findings of Study 1 by repeating the analysis using a larger sample, more representative of the UK population in terms of age, gender, and ethnicity. Beyond confirming the reappraisal pathway, Study 2 also revealed that ECBs mediated these relationships, with supportive parental responses predicating stronger beliefs in the controllability of emotions, subsequently predicting greater reappraisal use and lower depression. These findings extend our understanding of the mechanisms linking early emotion socialisation to later mental health outcomes while highlighting the importance of supportive parental responses for long-term outcomes.